An Analysis of Imitation Behavior Among Korean Drama Fans at the Ratu Sepudak Student Dormitory in Pontianak City - Mahadina, Cintia; Wiyono, Hadi; Zatalini, Adhalia; Bahari, Yohanes; Utami, Patrisia Rahayu (Universitas Tanjungpura, 2025)
This study aims to analyze the factors that cause imitative behavior among Korean drama fans at the Ratu Sepudak Female Student Dormitory in Pontianak City. The phenomenon of imitating Korean culture, particularly through Korean dramas, is increasingly prevalent among teenagers and female students. This study uses a qualitative research method. Data were collected through in-depth interviews with four informants selected based on the criteria of intensity of watching Korean dramas and active involvement in Korean culture. The results of the study show that there are four main factors that influence imitative behavior, namely: (1) personal interest, which is related to interest in fashion, makeup, and character traits; (2) emotional needs, where Korean dramas become an escape when experiencing stress or boredom; (3) the influence of social media, which reinforces interest in Korean culture and encourages consumerism of Korean products; and (4) the social environment, especially friends in the dormitory who reinforce imitative behavior collectively. These four factors interact and contribute to shaping the informants' lifestyle, daily behavior, and adopted values. This study is expected to provide insight for academics, dormitory managers, and students regarding the dynamics of imitating foreign popular culture, as well as serve as a consideration in developing a selective and critical attitude in consuming foreign culture.